Adopting the bottom-up approach and cluster analysis on North American and European male serial killers - Taylor, Sadie; Cahillane, Marie; Workman, Lance (JSciMed Central, 2017)
This study explores the application of the FBI’s organised-disorganised classification to North-American and European male serial killers. Adopting the same method as Taylor, Lambeth, Green, Bone and Cahillane’s 2012 study, 52 crime scene criteria were used to categorise the murders committed by 25 male European and 25 male North-American serial killers. Applying content analysis, murders committed were dichotomously coded for the presence or absence of crime scene criteria using numerous secondary sources. Two separate agglomerative hierarchical cluster analyses using Ward’s method as the clustering algorithm formed two clusters for the North-American and two for the European serial killers. There were differences in the crime scene criteria for clusters between North-American and European serial murders. The ‘bottom-up’ approach resulted in clusters from the crime scene criteria demonstrating that there are problems associated with classifying traits as simply organised and disorganised. All clusters comprised of a degree of core organised traits -consistent with Canter, Alison, Alison and Wentink’s (2004) assumption that all serial killings require a degree of organisation. Further examination of frequency of occurrence measures suggests there are subtle but inherent differences between the MO of North American and European serial killers.
Keywords: Offender profiling; Serial killers; Cluster analysis